Implementation of Good Governance Principles in the Formation of Regional Regulations in Indonesia - SAKTI, Sawung Aji Bhawono; DEWI, Anak Agung Sagung Laksmi (PT Keberlanjutan Strategis Indonesia, 2025)
This study analyzes the implementation of good governance principles in the formation of Regional Regulations (Perda) in Indonesia with a focus on the aspects of transparency, public participation, and accountability. The research method uses a qualitative approach through document studies of 15 problematic Perda and in-depth interviews with 10 stakeholders in Bandung City and Sleman Regency. The results of the study indicate that the implementation of good governance principles is still low, where only 40% of regions are transparent in publishing Perda drafts, public participation reaches 25-30%, and accountability is recorded at 20%. The main obstacles include structural limitations (70% of regions do not have a policy analysis unit), cultural (bureaucratic resistance), and technical (limited human resource capacity). However, the study also identified good practices such as the E-Legislation system in Surabaya which increased youth participation by 40%, and the Perda Law Clinic in Yogyakarta which reduced problematic Perda by 35%. These findings conclude that institutional strengthening, increasing legislative capacity, and utilizing technology are the keys to realizing the formation of more participatory and accountable Perda. The study recommends three strategic steps: (1) the establishment of a regulatory analysis unit in each region, (2) technical training for Perda drafters, and (3) the development of a digital platform for public participation.